Pemanfaatan Ikan Asin Dalam Pembelajaran Bahasa Indonesia Di SD/MI - Ma’rifah, Farida Umu (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
The low ability of students to write sentences in Indonesia language learning is the background of this research. Salted fish learning resources are used to develop students’ writing sentence skills. Salted fish as part of local wisdom is an important given to the education. This study aims to examine the effectiveness of the use salted fish learning resources to make sentences in Indonesian language learning. The study was conducted in class III SDN Tambakreja 02 Cilacap with 25 students, consisting of 12 male and 13 female students. Data collection techniques were observation, interview and documentation. The collected data were analyzed using qualitative analysis techniques. The result of the study prove that salted fish learning resources are effective in developing students’ writing abilities. High student enthusiasm, seen from a pleasant atmosphere and student activity in the learning process. The percentage of students who score above KKM is 92% of 25 students.